Penyelakuan Sistem Saliran Ribut Untuk Kompleks Industri Perai Menggunakan Storm Water Management Model (XP-SWMM) - Mahat, Masita (Universiti Sains Malaysia, 2005)
The Storm Water Management Model (SWMM) is applied in this project to develop a model for an urban drainage system to analysis runoff quantity for Kompleks Industri Perai. The Storm Water Management Model (SWMM) was developed for the EPA between 1969 and 1971 and was the first comprehensive model for urban runoff analysis. This model can simulate all aspects of the urban hydrologic and water quality cycles, including rainfall, snowmelt, surface and subsurface runoff, flow routing through the drainage network, storage and treatment. In this project, an urban drainage system model is developed to analyse the discharges of urban storm water runoff for Kompleks Industri Perai. The simulations were performed using design rainfall for 10 years ARI and 50 years ARI. The results from both simulations can be analyzed and compared. The analysis of water quantity gives the maximum discharges flows of 24.93 m3/s for 10 years ARI and 26.98 m3/s for 50 years ARI.